A 96‐week randomized trial of switching to entecavir in patients who achieved virological suppression on lamivudine therapy. Issue 4 (April 2016) - Ahn, Sang Hoon; Heo, Jeong; Park, Jun Yong; Woo, Hyun Young; Lee, Heon Ju; Tak, Won Young; Um, Soon Ho; Yoon, Ki Tae; Park, Soo Young; Kim, Chang Wook; Kim, Hyung Hoi; Han, Kwang‐Hyub; et al.
Abstract: Background and Aim: There are limited data assessing whether patients who achieved virological suppression on lamivudine but remain hepatitis B "e" antigen‐positive should be switched to a more potent antiviral with a high genetic barrier to resistance or continue with lamivudine. We compared the safety and efficacy of switching with entecavir versus continuing lamivudine. Methods: This was a Phase IV, randomized, open‐label, prospective study in a tertiary care setting. Seventy‐three chronic hepatitis B patients who achieved virological suppression on lamivudine (serum hepatitis B virus DNA < 60 International Unit (IU)/mL) were enrolled. Entecavir or lamivudine were administered orally for up to 96 weeks. Virologic and serologic responses were measured throughout the study. Results: A significantly higher proportion of patients in the entecavir group achieved hepatitis B virus DNA < 60 IU/mL at Weeks 48 (100% [38/38] vs 62.8% [22/35]; P < 0.001) and 96 (97.4% [37/38] vs 57.1% [20/35]; P <0.001). A greater number of patients had virologic breakthrough (Week 96 cumulative incidence 42.9% vs 2.6%; P <0.001) and genotypic lamivudine resistance (28.6% [10/35] vs 0% [0/38]; P <0.001) in the lamivudine group. No serious adverse events or laboratory abnormalities were reported. Conclusions: Even after achieving virological suppression on lamivudine therapy, the risk of emergent lamivudine resistance increases over time. Switching to entecavir resulted in a maintained virologic response and superior serologic responses versus continued lamivudine therapy. This study supports a rationale for switching to entecavir in chronic hepatitis B patients with virological suppression on lamivudine.